The Wind‐Dependent Surface Drag Coefficient Contributes to the Secondary Eyewall Formation in Tropical Cyclones: A Case Study of Typhoon Gaemi (2024) - Hui Wang; Yuqing Wang; Hongxiong Xu; Dajun Zhao; Jia Liang; Tzu‐Hsiung Yen (Geophysical Research Letters, 2025)
Abstract This study explores how a wind‐dependent surface drag coefficient (CD) influences secondary eyewall formation in tropical cyclones (TCs), using Super Typhoon Gaemi (2024) as a case study. We employ the Weather Research and Forecasting model with two different CD parameterizations and find that changing CD markedly affects boundary‐layer convergence and outer rainband evolution. In particular, the latest CD scheme with larger surface drag coefficient at wind speeds less than 45 m s−1 yields higher surface stress and stronger boundary‐layer convergence in the outer core, thereby enhancing rainband convection and triggering earlier formation of a more coherent secondary eyewall structure compared to the scheme with smaller, nearly constant CD at wind speeds greater than 45 m s−1. These findings underscore the fundamental role of surface friction in shaping TC structure, with direct implications for operational TC forecasting, especially during eyewall replacement cycles.